Habitual- and Meal-Specific Carbohydrate Quality Index and Their Relation to Metabolic Syndrome in a Sample of Iranian Adults - Majdi, Maryam; Imani, Hossein; Bazshahi, Elham; Hosseini, Fatemeh; Djafarian, Kurosh; Lesani, Azadeh; Akbarzade, Zahra; Shab-Bidar, Sakineh (Frontiers in Nutrition, 2022)
Aims: Most studies on diet quality have focused on the habitual and overall intake of foods without considering intakes at specific eating occasions. The aim of this study was to assess the association between habitual and meal-specific carbohydrate quality index (CQI) and metabolic syndrome (MetS) in Iranian adults. Methods: In this cross-sectional study, data from 850 participants were analyzed. Dietary information was obtained from a 3-day non-consecutive 24 hours recall. CQI was calculated from three criteria: dietary fiber, glycemic index, and solid carbohydrate/total carbohydrate ratio. The association between CQI and MetS was assessed by logistic regression. Results: The prevalence of MetS in the lowest and highest tertile of CQI were 30.1 and 33.7, respectively (P=0.6). In habitual diet and all three meals, we failed to find any significant association between tertiles of CQI and MetS either before or after adjustment for covariates. However, in the habitual meal (OR: 0.69, 95%CI: 0.47-0.96) and lunch meal (OR: 0.66; 95%CI: 0.47-0.94), the highest CQI in comparison to the lowest one, significantly decreased the low-HDL. In addition, the trend of low-HDL with CQI in habitual meal and lunch meal was statistically significant. Conclusion: The results of this study showed that CQI was not associated with MetS and its components. Further investigations into the mechanisms underlying the role of carbohydrate quality in developing metabolic disorders are warranted.